DUE DILIGENCE INVESTIGATION OF ECONOMIC AND INSTITUTIONAL RESTRAINING FACTORS OF AGRICULTURAL DEVELOPMENT IN UKRAINE - Rudevska , Viktoriia; Pohorila , Olena (Socio-economic relations in the digital society, 2021)
The purpose of the article is to analyze the current state of the insurance market of the agro-industrial complex in Ukraine and identify problems that slow down its development. The articles examine the state of voluntary insurance of the agro-industrial sector of Ukraine’s economy. Legislative necessity of existence of the Agrarian insurance pool and its influence on volumes of insurance of the agricultural industry are analyzed. The role of state support for agricultural insurance for the period 2017—2019 and its impact on competition in the insurance market, as a result — how it correlates with an increasing / a decreasing the need for lending are also analyzed in the article. It is proved that the development of agricultural insurance should be aimed at creating favorable and safe conditions for doing business by all participants in the agricultural market, which provides for the distribution of risks between farmers, banks, insurance companies and the state. By analyzing the competitive principles of obtaining financial support by farmers from the state, which are provided by budget allocations and the strategy of state support of the agricultural sector for 2021—2023, concluded that such conditions are not transparent and freely available to all farms and other organizational and legal forms of agro-industrial complex of Ukraine. It is sumed-up that the demand of agricultural producers in compensation funds through the mechanism of cheaper loans is several times higher than the actual allocated allocations. There is a well-founded need to establish special requirements for policyholders of the agro-industrial segment in order to reduce the cost of insurance products and to provide free access to credit resources for farms. It is justified to introduce special requirements for policyholders of the agro-industrial segment in order to improve the quality and supply of insurance products, and as a consequence of creating free access to credit resources for agriculture, which will be the subject of further research.
Keywords: agro-industrial complex; agricultural entrepreneurship; insurance; lending; insurance companies